2012
DOI: 10.1143/jjap.51.01ad01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitridation of Si Nanoparticles on the Performance of Quantum-Dot Sensitized Solar Cells

Abstract: Two methods, the Method of Effective Trajectories and the Method of Distorted Particle Flux, are suggested for calculation of cross-sections of n-n'transitions between Rydberg states of multicharged ions induced by electron impact. These methods are based on rectilinear trajectories with effective impact parameter and effective velocity. The difference between direct calculations of CoulombBom cross-sections and these methods for transitions with principal quantum numbers n,n' Q 6 is about 10-20%. Calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Since the low-dimensional Si quantum dots (Si QDs) have quantum confinement effect, the band gap of Si QDs can be tunable by controlling the dot size, which provides an effective way to adjust the energy band structures by changing the Si QDs size to get better spectral matching [ 2 , 3 ]. It was reported that the broadband spectral absorption can be realized by forming the all Si-based tandem type solar cells, whose power conversion efficiency can exceed the Shockley-Queisser limit [ 4 - 6 ]. In the present stage, it is interesting to study the photovoltaic properties of Si QDs-based structures for their actual applications in devices.…”
Section: Introductionmentioning
confidence: 99%
“…Since the low-dimensional Si quantum dots (Si QDs) have quantum confinement effect, the band gap of Si QDs can be tunable by controlling the dot size, which provides an effective way to adjust the energy band structures by changing the Si QDs size to get better spectral matching [ 2 , 3 ]. It was reported that the broadband spectral absorption can be realized by forming the all Si-based tandem type solar cells, whose power conversion efficiency can exceed the Shockley-Queisser limit [ 4 - 6 ]. In the present stage, it is interesting to study the photovoltaic properties of Si QDs-based structures for their actual applications in devices.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that surface quality of nanostructures has a significant influence on related device performance. Several pioneer works on Si NC-based device have shown that the performance can be further improved through proper Si NCs surface treatment [35][36][37][38]. In this work, we demonstrate that controlled particle oxidization can be employed as an easy and effective way for surface passivation.…”
Section: Introductionmentioning
confidence: 66%
“…First, we investigated the photo response of ZnInON/ZnO MQWs. 4, respectively, which demonstrates the high photosensitivity of the ZnInON/ZnO MQWs. We observed that the poly-crystalline ZnO has quite large surface roughness (root mean square roughness (RMS): 13.1 nm), that is, large haze, whereas the single-crystalline ZnO has atomically flat surface of RMS = 0.16 nm.…”
Section: Photo-electrical Properties Of Zninon/zno Mqwsmentioning
confidence: 87%
“…Solar cells with low-cost and ultra-high conversion efficiencies, so-called "third generation solar cells", have attracted attention because of the potential to bring significant reduction in the electricity generation cost [1][2][3][4][5]. In single band gap devices that dominate the current photovoltaic market, choice of the material composing solar cells is a trade-off between maximizing current output with a narrow band gap material and voltage output with a wide band gap material.…”
Section: Introductionmentioning
confidence: 99%